Flavonoid and alkaloid constituents from Croton genus: chemical structures and biological activities - NGUYEN, Duy Hieu; NGUYEN, Thi Hong Van; PHAM, Thi Hong Minh (Vietnam Journal of Science and Technology, 2025)
The Croton genus (Euphorbiaceae) comprises more than 1,300 species distributed worldwide, especially in tropical and subtropical regions. These species are rich in secondary metabolites, notably flavonoids and alkaloids, which contribute significantly to their wide range of traditional medicinal uses. This review aims to provide a comprehensive overview of Croton species in terms of their botanical characteristics, traditional uses, phytochemical diversity, and pharmacological potential. The review focuses on the structural diversity and biological activities of flavonoids and alkaloids, highlighting their role in anti-inflammatory, antioxidant, antimicrobial, anticancer, and neuroprotective effects. Furthermore, the review outlines the current preclinical research status and emphasizes the need for further investigations into the pharmacokinetics, toxicity, and mechanisms of action of these promising natural compounds.